Web application for organizing bilingual presentations - Boichura, Mykhailo; Lopatina, Diana (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
The importance of creating new hardware and software tools for teaching English is substantiated. A corresponding web application for management and edit the presentations is proposed. This can contribute to more effective bilingual education. The structure of the web application, the corresponding technology stack, the data schema are described, and the principles of working with the site are explained in general.